THE EFFECT ON CURRENT ACCOUNT OF NET TOURISM REVENUES IN TURKEY - Mehmet Cihangir; Birol Erkan; Melda Harbalıoglu (European Scientific Journal, ESJ, 2014)
Tourism is one of the important sectors of the national economy in terms of its contribution to the national revenue. Tourism revenues, particularly in economies that have problems with the export of value-added products provide foreign exchange inflow and play an important role in the financing and reducing foreign trade deficit and current account deficit. Net tourism revenues in Turkey and its effects on balance of payments and current account were analyzed. VAR analysis method was used to determine the relationship between variables. In addition, Granger causality and impulse-response analysis of the degree and direction of the relationship was tested. The analyzes performed and the resulting scores revealed tourism revenues having positive effects on the current account.